PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEKERASAN SEKSUAL OLEH UNIT PELAKSANA TEKNIS DAERAH PERLINDUNGAN PEREMPUAN DAN ANAK KOTA DUMAI - Sri Asma Harahap; Syaifullah Yophi; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Children are buds, potentials, and the younger generationto continue the ideals of the nation, have strategic roles and have specialcharacteristics and characteristics that guarantee the continued existenceof the nation and state in the future. Children are a portrait of the nation'sfuture in the future, the next generation of the nation's ideals, so that everychild has the right to survive, grow and develop, participate and is entitledto legal protection.This type of research can be classified as sociological legalresearch, because this research was conducted by looking at the effect ofthe enactment of positive laws on people's lives. This sociological researchexamines the legal protection of child victims of sexual violence by theRegional Technical Implementation Unit for the Protection of Women andChildren. The data sources used are primary data, secondary data, datacollection techniques in this study are interviews, the data used is primaryprocessed data.From the results of the research conducted, it can beconcluded, First, legal protection in the form of Juridical or LegalServices, Medical Services and Psychological Services. Second, theobstacles faced are internal factors such as a lack of human resources(employees) and limited funding sources. external factors in the form ofchildren not realizing they are victims, fear of not obeying the perpetrator,low legal awareness on the part of victims of society, public distrust oflegal protection and lack of awareness of cases of child victims of sexualviolence. Third, efforts to overcome obstacles include improving internaldeficiencies, namely increasing human resources (employees), managingthe available budget, increasing the responsibility of the UPTD PPA. Andexternal shortcomings, namely socialization in the region, providingoutreach in schools, carrying out campaigns in the mass media.Keywords: Legal Protection - Child Victims of Sexual Violence